Post concussion syndrome following mild traumatic brain injury in Emergency Department HUSM - Heng@Heng, Chua Swee@Goh Swee (2016)
Introduction: Post-concussion syndrome is a treatable yet debilitating complication that is frequently seen in patients who sustained mild traumatic brain injury. Proper defining, evaluating and managing these patients and its associating factors can alter clinical course and severity of the illness. Various clinical tools were developed to aid proper diagnosis and management of these patients. Purpose: To determine the incidence of post-concussion syndrome and its association risk factors in patients presenting with a mild traumatic brain injury to the Emergency and Trauma Department Hospital USM. Materials and methods: In this prospective cohort study, we recruited patients with mild traumatic brain injury, who fulfilled the inclusion and exclusion criteria, admitted directly or referral from local clinics to the Emergency and Trauma Department Hospital USM. Baseline interviews were conducted on those eligible consented patients to gather information on demographic data, type of injury and risk factors on the day of injury. Subsequent telephone interviews were carried out within 2 weeks after the initial presentation and postconcussion symptoms were documented using the Rivermead Post-Concussion Symptoms Questionnaires as the measurement tool. Present of three or moresymptoms were considered as post-concussion syndrome. Statistical analyses were performed by using a simple and multiple logistic regressions. Adjusted OR and 95% CI were computed, and a p-value of less than 0.05 was set. Results: A total of 113 patients with mild traumatic brain injury were included in this study, but only 80 patients have completed the study due to various reasons. 16.3% of the patients have three or more post-concussion symptoms at 2 weeks post mild TBI. The most common presenting symptoms were headache (30%), feeling of dizziness (28.7%), fatigue, tiring more easily (8.8%), nausea and/or vomiting (7.5%), and sleep disturbance (7.5%). Among the risk factors examined, previous history of concussion was statistically significant for post-concussion syndrome. Patients with previous history of concussion are 4 times more likely to experience Post-Concussion Syndrome as compared to those without a previous history of concussion. Conclusions: Our study suggested that the incidences of post-concussion syndrome among patients with mild TBI are high, with previous history of concussion as the predictive risk factors for the patients with mild TBI to develop post-concussion syndrome.